ILLOCUTIONARY ACT ANALYSIS OF JOKOWI THREE PERIODS ON CNBC NEWS 2022: CRITICAL DISCOURSE ANALYSIS - Benny Dele Bintang Ananta (University of Muhammadiyah Malang, 2023)
This paper discusses the highly controversial issue of postponing the 2024elections. The postponement of the election was replaced with the discourseof extending President Joko Widodo's leadership term.The major objective of this study is to categorize various illocutionary actsand provide a concise description of how they are used by speakers in CNBCnews content. In this investigation, the author uses descriptive qualitativeresearch techniques to collect and dissect information from writing with thetitle